PERANCANGAN INSTRUKSI KERJA DOKUMEN DAN VISUAL PADA MESIN ELECTRICAL DISCHARGE MACHINE - Ahmad Padhil; Nurhayati Rauf (Journal of Industrial Engineering Management, 2020)
Quality is a factor that can increase product competitiveness. In improving products quality is necessary to control the quality (Quality Control) of the process activities. This study aims to determine the quality control of granulated sugar packaging process by using the seven tool method consisting of check sheet, histogram, Pareto chart, flow chart, scatter diagram, control chart and fishbone diagram. From 30 days observation concluded that the highest type of damage consist of metal detection by 145 bags and torn packaging by 50 bags. Then, from the results of control chart known that out of control process still happen. Both types of damage then revised, and process capability analysis is carried out, so can be concluded that the process is not capable in making the product according to specifications. Therefore, an analysis using fishbone diagram shows that the causes of damage are human, working methods, and machines. From these factors, Standard Operating Procedures can be done as well as designing new machines in packaging process